Music in medieval Europe - Yudkin, Jeremy (New Jersey Prentice Hall, 1989)
Music in Medieval Europe combines a cultural history of the Middle Ages and in-depth scholarship on the music and leading composers active during the period. It includes an integrated anthology of key works with approachable and enlightening explanations, making it easily accessible for both beginning and advanced students. Its chronological organization, broad scope, and detailed music analyses make Music in Medieval Europe an ideal introductory text.